2013 International Workshop on Biometrics and Forensics (IWBF) 2013
DOI: 10.1109/iwbf.2013.6547323
|View full text |Cite
|
Sign up to set email alerts
|

Targeted biometric impersonation

Abstract: When applying biometric algorithms to forensic verification, false acceptance and false rejection can mean a failure to iden tify a criminal, or worse, lead to the prosecution of individuals for crimes they did not commit. It is therefore critical that bio metric evaluations be performed as accurately as possible to determine their legitimacy as a forensic tool. This paper ar gues that, for forensic verification scenarios, traditional per formance measures are insufficiently accurate. This inaccu racy occurs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A recent conference paper has shown that this attack is also effective against face verification [4]. This paper is an expansion of that publication.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…A recent conference paper has shown that this attack is also effective against face verification [4]. This paper is an expansion of that publication.…”
Section: Introductionmentioning
confidence: 92%
“…This paper is concerned with two situations in forensics that significantly increase the chances of false positives being reported. One is targeted biometric impersonation [4] and the other is as a result of individuals being preselected for assessment. Targeted biometric impersonation involves locating an innocent person in the verification system with a similar biometric signature and then fraudulently assuming that identity to spoof a verification check.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of targeted attacks has been studied for both face [3] and gait verification systems [9]. In the case of gait verification the attack was used with another impersonation method to create the first successful spoofing attempt against that biometric.…”
Section: Introductionmentioning
confidence: 99%